Evaluation of cell blocks from effusion specimens in Gynecologic Oncopathology: An experience of 220 cases, diagnosed at a Tertiary Cancer Referral Center. - Rekhi, Bharat; Karmarkar, Srushti; Gupta, Chhavi; Deodhar, Kedar; Menon, Santosh; Pathuthara, Saleem; Maheshwari, Amita; Shylasree, T; Gupta, Sudeep; Deodhar, Kedar K; Shylasree, T S (Indian Journal of Pathology & Microbiology)
One of the common indications of ascitic fluid examination in gynecological oncopathology is the detection and classification of malignant cells, especially in cases of clinically suspicious tubo-ovarian masses. The present study was undertaken to assess and validate the diagnostic utility of cell blocks (CBs) and compare its results with the corresponding conventional smears, prepared from effusion samples. CBs were prepared by thromboplastin technique in 220 cases. In 208 cases, diagnostic concordance between results obtained from smears and corresponding CBs was evaluated. Various antibody markers were tested, as per individual case. The average age of patients was 52.2 years. Positive immunohistochemical (IHC) staining for various markers was observed in 182 cases (82.7%) The most frequently positive antibody marker was PAX8 (101/134), followed by p53 (85/92) [mutation type (either diffusely positive or completely negative)], WT1 (tumor cells) (80/112), calretinin (2/87) (diffuse), BerEP4 (21/49), CA125 (21/24), CK7 (31/39) and CK20 and CDX2, together (5/16). Various other IHC markers utilized, including their positive expression, were TTF1 (1/10), p40 (3/3), p63 (2/4), ER (21/29), HBME1 (1/7), GATA3 (1/4), and MIC2 (1/1). Complete diagnostic concordance between CBs and smears was observed in 170/208 cases (81.7%). There were 20 major discordances, 10 minor and 8 cases with sampling errors. IHC was useful in classifying 158/182 (86.8%) cases, including serous or Müllerian adenocarcinoma (n = 123), mostly high-grade (121); metastatic squamous carcinoma (3); gastrointestinal-type adenocarcinoma (8); pulmonary adenocarcinoma (1); breast adenocarcinoma (1); Ewing sarcoma (1); and mesothelioma (2). CBs are complementary to smears in the detection of gynecological malignancies, mostly high-grade serous adenocarcinomas. These provide an opportunity for testing several IHC markers, for a precise diagnosis, including in various uncommon case scenarios, associated with significant therapeutic implications.